Nunavut Urban Futures: Vernaculars, Informality and Tactics (Research Note) - Sheppard, Lola (Études Inuit Studies)

(untitled) (Centre interuniversitaire d’études et de recherches autochtones (CIÉRA), 2020)
The Canadian Arctic, and Nunavut in particular, is one of the fastest-growing regions per capita in the country, raising the question as to what might constitute an emerging Arctic Indigenous urbanism. One of the cultural challenges of urbanizing Canadian North is that for most Indigenous peoples, permanent settlement, and its imposed spatial, temporal, economic, and institutional structures, has been antithetical to traditional ways of life and culture, which are deeply tied to the land and to seasons. For the past seventy-five years, architecture, infrastructure, and settlement form have been imported models serving as spatial tools of cultural colonization that have intentionally erased local culture and ignored geographic specificities. As communities in Nunavut continue to grow at a rapid rate, new planning frameworks are urgently needed. This paper outlines three approaches that could constitute the beginning of more culturally reflexive planning practices for Nunavut: (1) redefining the northern urban vernacular and its role in design; (2) challenging the current top-down masterplan by embracing strategies of informal urbanism; and (3) encouraging planning approaches that embrace territorial strategies and are more responsive to geography, landscape, and seasonality.